DEVELOPING THE STORYTELLING MEDIA FOR TEACHING VOCABULARY MASTERY FOR IX GRADE AT JUNIOR HIGH SCHOOL STUDENTS - Evi Liana Sari evi (IKIP Siliwangi, 2024)
The objectives of this study were to determine the following: (1) the use of audiovisual media; (2) the application of audiovisual media; and (3) the impact of audiovisual narrative media on vocabulary acquisition both before and after using the product. This study involved both research and development.This study used both quantitative and qualitative methods, designing research and development utilising the Borg & Gall paradigm. There were three stages to this study project: fundamental research, design and development research, and experimental research. This study employed the Borges and Gall Research and Development (R&D) approach to gather data through the use of an unstructured interviewing tool and questionnaire.There are a few steps involved in using it.The procedures were as follows: (1) gather data (analysis process required utilising data from questionnaires, pre- and post-tests, and other sources), (2) develop product design, (3) validate product design, (4) test product (teaching and learning process), (5) revise product design, and (6) final product.Students in junior high school's IX grade are the subject of the research. This study's scope is limited to creating narrative material for junior high school students in the IXth grade. The final book that can be used to teach junior high school students about vocabulary mastery in the IX grade is this one.